Efecto del aceite de Salvia hispánica (chía) sobre la membrana corioalantoidea de Gallus gallus domesticus - Rivera Martinez, María del Pilar (2017)
The present study aimed to determine the effect of Salvia hispanica (chia) on the chorioallantoic membrane of Gallus gallus domesticus, using experimental research, with increasing stimulation. Seventy embryonated eggs of Gallus gallus domesticus were extracted 3 ml of albumin, then incubated for 7 days, at the end of which they were distributed into 6 groups of 6. To each group the pellets were instilled with 30 μl of the different treatments: White group (ultrapure water), control group (chloroform), standard group (Captopril), 03 groups problems (Salvia hispanica oil at concentrations of 27.81 mg / ml, 55.62 mg / ml and 83.43 mg / ml respectively). Subsequently, they were incubated for three more days, according to the procedure. On day twelve they were removed from incubator and the pellets were removed to perform observation of the chorioallantoic membrane through stereoscope and quantification of respective blood vessels. The obtained data were processed statistically by analysis of variance (ANOVA), and the Tukey test, with a confidence interval of 95% using the statistical software SPSS version 21, comparing all the data of the groups with each other, besides the analysis with the Boxplot chart. A p = 0.000 of a p <0.05 was obtained, for which it is inferred that there is an influence of the treatments on the antiangiogenic potency, by means of the Tukey test it was established that the oil group of Salvia hispanica (chia) at concentration of 55.62 mg / ml has the same antiangiogenic potency with the standard (captopril). It was concluded that Salvia hispanica oil has an antiangiogenic effect on the chorioallantoic membrane of Gallus gallus domesticus, with a higher potency at 55.62 mg / ml